The Impact of Behavioral Factors on Stock Investment Decision: Evidence from Individual Investors in Nepal - Chand, Prakash (Myagdi Guru, 2024)
Behavioral finance, a field integrating psychology into financial theory, explores how cognitive biases and emotional responses influence investor behavior and market dynamics globally, including in emerging markets like Nepal. This study focuses on key behavioral biases of the most influencing factor on stock investment decisions at NEPSE is herding behavior, as it exhibits the strongest impact with a beta coefficient of 0.463, indicating a substantial influence on investor behavior, overconfidence, loss aversion, herd behavior, anchoring, and risk perception and their impact on investment of Nepal stock exchange. Behavioral factors significantly influence stock investment decisions among Nepali investors, impacting market efficiency and growth potential at NEPSE. This study employs descriptive and analytical research to characterize investor behavior and assesses the relationships between biases and investment outcomes. A sample of 384 NEPSE investors was surveyed, using structured questionnaires and SPSS for analysis. Findings underscore the importance of enhancing financial literacy, investor education, and regulatory measures to mitigate biases’ adverse effects, thereby improving market stability and efficiency. Despite its focus on NEPSE, limitations include the need for broader market generalizability and consideration of additional variables affecting market dynamics. Future research should expand scope and sample size to enhance reliability and applicability across diverse financial contexts.